Mobile Health Services in Turkey During the Earthquakes in Van - Dursun, Recep; Karadas, Sevdegul; Gonullu, Hayriye; Sevimli, Sukran; Guner, Savas; Cetinkaya, Orhan (Annals of Medical Research, 2021)
None
Keywords: None